Properties Tests and Mathematical Modeling of Viscoelastic Damper at Low Temperature With Fractional Order Derivative - Xu, Yeshou; Dong, Yaorong; Huang, Xinghuai; Luo, Ying; Zhao, Shiwei (Frontiers in Materials, 2019)
In the present paper, several dynamic properties tests of the viscoelastic damper at -5oC are conducted under different frequencies and displacements to investigate the dynamic behavior of the viscoelastic damper at low temperature. The seven-parameter fractional derivative model is modified with the temperature-frequency equivalent principle and utilized to describe the dynamic properties of the viscoelastic damper. The 9050A and ZN22 viscoelastic materials are used to verify the modified seven-parameter fractional derivative model. The experimental and numerical results reveal that the viscoelastic damper has perfect energy dissipation capacity at low temperature, and the modified seven-parameter fractional derivative model can well capture the dynamic behavior of viscoelastic materials and dampers.